MODEL PENGEMBANGAN EKOWISATA DALAM MENDUKUNG KEMANDIRIAN EKONOMI DAERAH STUDI KASUS PROVINSI DIY - Joko Tri Haryanto (Universitas Gadjah Mada, 2014)
Along with the development and economic growth processing, the role of tourism nowadays is moreessential, as new sectors that contibuting foreign exchange for the improvement of people’s welfare.Indonesia is one country that has a many natural and cultural remarkable, also enjoy this benefit.However, tourism is often regarded as one of the largest damage contributor to the preservation of theenvironment and the community, particularly through the development of the infrastructure. YogyakartaProvince as one of the tourist destinations, also face the same problem, a shift in cultural values , socialand environmental wisdom. Ecotourism then regarded as one of the policy alternatives that can be usedas a solution to this problem. By using a qualitative approach, this study was conducted with the aim offormulating a model-based sustainable ecotourism cultural values , social, and environmental wisdomthat will support the successful development of tourism in Yogyakarta. With the development of thispolicy model, expected to be a guideline for governments in developing national policies in the field ofsustainable tourism in order to streng then the economic independence in the region